Levetiracetam Use in the Critical Care Setting - Szaflarski, Jerzy P.; DeWolfe, Jennifer L. (Frontiers in Neurology, 2013)
Intravenous (IV) levetiracetam (LEV) is currently approved as an alternative or replacement therapy for patients unable to take the oral form of this antiepileptic drug (AED). The oral form has Food and Drug Administration (FDA) indications for adjunctive therapy in the treatment of partial onset epilepsy ages 1 month or more, myoclonic seizures associated with juvenile myoclonic epilepsy starting with the age of 12 and primary generalized tonic-clonic seizures in people 6 years and older. Since the initial introduction, oral and IV LEV has been evaluated in various studies conducted in the critical care setting for the treatment of status epilepticus, stroke-related seizures, seizures following subarachnoid or intracerebral hemorrhage, post-traumatic seizures, tumor-related seizures, and seizures in critically ill patients. Additionally, studies evaluating rapid infusion of IV LEV and therapeutic monitoring of serum LEV levels in different patient populations have been performed. In this review we present the current state of knowledge on LEV use in the critical care setting focusing on the IV uses and discuss future research needs.